(untitled) (Research, Society and Development, 2021)
The bean plant is a nutrient-demanding plant due to its shallow root system and short cycle. Manganese and zinc deficiency can reduce metabolic activity due to the demand on physiological processes. Sulfur can limit crop productivity. This study aimed to evaluate the performance of common bean under different doses of foliar fertilizer applied at two phenological stages. The design used was the DBC with four replications and the treatments were 5 doses of foliar fertilizer (0; 0.250; 0.500; 0.750; and 1 L ha-1) in two phenological stages of application (V4 and R5). As a source of Mn, Zn and S, the foliar fertilizer GRAIN SET® was used. After 102 days of sowing, harvesting was carried out manually, and the grains were air-dried at 13% humidity. The variables analyzed were: plant height (m), number of pods per plant, number of grains per pod, mass of 1000 grains (g) and yield (kg ha-1). In relation to the phenological stages V4 and R5, only the variable number of pods per plant had a significant difference. For mass of one thousand grains and yield there was a significant effect. The productivity was between 3437.59 and 5543.58 kg ha-1. This increase in productivity is explained by the presence of zinc in the foliar fertilizer. The dose of 0.5 L ha-1 for mass of one thousand grains obtained the best performance at a weight (285.40 g).